1993
DOI: 10.1017/s0022215100123011
|View full text |Cite
|
Sign up to set email alerts
|

Pneumoparotitis, subcutaneous emphysema and pleomorphic adenoma

Abstract: Self-induced pneumoparotitis is a distinct clinical entity which should be considered in any inflammatory swelling of the parotid gland. When complicated by subcutaneous emphysema, other more important causes should be excluded. An unusual case is presented, which was further complicated by the presence of a pleomorphic adenoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Under physiological conditions, air and oral secretions are prevented from flowing back into the parotid duct and gland by various anatomical mechanisms: contraction of the buccinator muscle [8], the diameter of the duct orifice is less than that of the duct itself [7,9], the duct orifice is slit-shaped and is sealed off by mucosal folds when intraoral pressure increases [4,5], cheek inflation increases duct angle both between the oral submucosa and buccinator muscle and between the buccinator and the subcutaneous tissue alongside the masseter muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Under physiological conditions, air and oral secretions are prevented from flowing back into the parotid duct and gland by various anatomical mechanisms: contraction of the buccinator muscle [8], the diameter of the duct orifice is less than that of the duct itself [7,9], the duct orifice is slit-shaped and is sealed off by mucosal folds when intraoral pressure increases [4,5], cheek inflation increases duct angle both between the oral submucosa and buccinator muscle and between the buccinator and the subcutaneous tissue alongside the masseter muscle.…”
Section: Discussionmentioning
confidence: 99%
“…As possible causes of appearances and recurrences of parotid involvement, there is a weakening of the buccinator muscle that does not prevent the retrograde flow toward the Stensen duct and the presence of an abnormal dilation in the ducts path. 8 It is suspected that at the submandibular level, the possible causes would be a dilatation of the duct as anatomical variation or secondary to a trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Tomography report stated that inside the submandibular salivary gland, a hypodense image, gas density (-1100 UH) was observed, dilating the gland and also the Wharton's duct, measuring 3.95 Â 4.47 Â 4.68 cm considering emphysematous sialoadenitis (►Figs. [4][5][6][7][8][9].…”
Section: Case Reportmentioning
confidence: 99%
“…Several predisposing factors for pneumoparotid disease have been reported in the literature. These factors include a patulous duct, congenital abnormality, hypotonia of the buccinator muscle around the papilla, hypertrophy of the masseter muscle, self-injury to the Stensen's duct, decreased production of saliva with increased mucous secretion, transient obstruction of Stensen's duct by mucous plugs causing decreased salivary flow, diagnostic maneuvers such as sialography [21,23,39,48,90], blunt trauma to the cheek [24], pleomorphic adenoma [36], and treatment for duct stenosis with stent implantation or transoral duct surgery [162]. Sánchez et al [16] reported the case of a 15-year-old girl who injured herself by self-instrumentation of the parotid gland orifice with hairpins or safety pins.…”
Section: Predisposing Factors Of Pneumoparotidmentioning
confidence: 99%